2017
DOI: 10.1002/hep.29269
|View full text |Cite
|
Sign up to set email alerts
|

Biases in the reporting of hepatocellular carcinoma tumor sizes on the liver transplant waiting list

Abstract: We investigate the possibility that patients with hepatocellular carcinoma (HCC) listed for liver transplant with tumors just outside Stage T2 size criteria may be inaccurately reported as just meeting the tumor size criteria for transplant. The UNOS/STAR database identified 12,958 patients listed for liver transplants with HCC exception points from 2006–2013, 9,168 of whom were listed with one tumor. A logistic power peak function was fitted to the single-tumor size histogram, with the fitted values represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…We observed in the UNOS‐DS cohort a relatively high proportion of patients with explant tumor stage beyond Milan criteria (33%), reflecting either pre‐LT under‐staging or inadequate response to down‐staging, as well as a higher 3‐year post‐LT HCC recurrence rate of 13% in this group versus 7% in the Milan group. Samoylova et al recently reported inaccuracies and biases in reporting tumor size by LT centers for patients meeting conventional LT criteria . Adherence to the endpoint of down‐staging to be within Milan criteria before LT and observing disease stability for at least 3 to 6 months are essential in minimizing the risks for tumor recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed in the UNOS‐DS cohort a relatively high proportion of patients with explant tumor stage beyond Milan criteria (33%), reflecting either pre‐LT under‐staging or inadequate response to down‐staging, as well as a higher 3‐year post‐LT HCC recurrence rate of 13% in this group versus 7% in the Milan group. Samoylova et al recently reported inaccuracies and biases in reporting tumor size by LT centers for patients meeting conventional LT criteria . Adherence to the endpoint of down‐staging to be within Milan criteria before LT and observing disease stability for at least 3 to 6 months are essential in minimizing the risks for tumor recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Samoylova et al recently reported inaccuracies and biases in reporting tumor size by LT centers for patients meeting conventional LT criteria. (31) Adherence to the endpoint of down-staging to be within Milan criteria before LT and observing disease stability for at least 3 to 6 months are essential in minimizing the risks for tumor recurrence. We found that within the UNOS-DS group, those from SWR and MWR had significantly worse post-LT survival compared with LWR.…”
Section: Discussionmentioning
confidence: 99%
“…We concluded that this subgroup at low risk for waitlist dropout did not warrant the same listing priority as others with T2 HCC. 37 43 then there is little doubt that bias in reporting radiographic response to LRT will emerge as well. Given that blood type was strongly associated with wait time and the MELD score at the time F I G U R E 3 Cumulative incidence of waitlist dropout with lowrisk group meeting all of the following at listing: MELD-Na < 15, Child-Pugh class A, single tumor 2-3 cm, and AFP ≤20 ng/mL TA B L E 4 Waitlist and explant characteristics between the low risk of dropout group and all other patients of LT, 31 we then restricted the analysis to patients with blood group O (longest expected wait time) who accounted for 45% of the overall cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a patient with a T2 HCC may be granted MELD exception but could then be subjected to a reduction in MELD exception points based on a favorable response to LRT. If there are already inaccuracies in reporting tumor size by LT centers for patients meeting conventional LT criteria, 43 then there is little doubt that bias in reporting radiographic response to LRT will emerge as well. The focus of the current study is to identify a subgroup at low risk for dropout, but there are still problems concerning the rest of the cohort in that they represent a highly heterogeneous population with a wide range of dropout risks but receive the same priority for LT.…”
Section: Discussionmentioning
confidence: 99%
“…Their earnings management tests rely on less restrictive assumptions than tests of abnormal accruals (e.g., Jones, 1991) and real activities management (e.g., Roychowdhury, 2006), thus yielding more credible inferences. 1 The distribution discontinuity approach is widely used to detect earnings management (e.g., Degeorge et al, 1999;Matsumoto, 2002;Leuz et al, 2003;Barth et al, 2008), analyze properties of the "suspect" observations just above the zero earnings benchmark (e.g., Roychowdhury, 2006;Zang, 2012), and study manipulation of other metrics such as marathon running times (Allen et al, 2017) and reported tumor sizes (Samoylova et al, 2017). Burgstahler and Dichev's (1997) test is based on the empirical histogram of earnings and cannot easily incorporate multiple explanatory variables.…”
Section: Introductionmentioning
confidence: 99%